Persistent effects of pre-Columbian plant domestication on Amazonian forest composition - Levis, Carolina; Costa, Flávia R.C.; Bongers, Frans; Peña-Claros, Marielos; Clement, Charles R.; Junqueira, André B.; Neves, Eduardo G.; Tamanaha, Eduardo K.; Figueiredo, Fernando O.G.; Salomão, Rafael P.; Castilho, Carolina V.; Magnusson, William E.; et al. (American Association for the Advancement of Science, 2017)
The extent to which pre-Columbian societies altered Amazonian landscapes is hotly debated. We performed a basin-wide analysis of pre-Columbian impacts on Amazonian forests by overlaying known archaeological sites in Amazonia with the distributions and abundances of 85 woody species domesticated by pre-Columbian peoples. Domesticated species are five times more likely to be hyperdominant than non-domesticated species. Across the basin the relative abundance and richness of domesticated species increases in forests on and around archaeological sites. In southwestern and eastern Amazonia distance to archaeological sites strongly influences the relative abundance and richness of domesticated species. Our analyses indicate that modern tree communities in Amazonia are structured to an important extent by a long history of plant domestication by Amazonian peoples.